An Evidence-Based Review on Selected Traditional Formulations against Pediculosis - Seyede Zahra Ayatollahi; Gholamhossein Yousefi; Parmis Badr (Tehran University of Medical Sciences, 2022)
Pediculosis is a growing social problem in both developed and undeveloped countries. Resistance to chemical treatments and toxicity of insecticidal compounds are reasons why alternative medications should be proposed for this parasitic infestation. This study attempted to investigate traditional anti-lice treatments, and draw together scientific insights into lice management through the study of Persian Medicine manuscripts. Lice infestation formulations were searched in seven traditional textbooks (al-Manṣuri fi al-ṭibb, al-Qanun fi al-ṭibb, Kamil al-ṣina'ah al-ṭibbiyah, Qarabadin  Kabir, Qarabadin Salehi, Makhzan al-Adviyeh, Eksir Azam) pertaining to one millennium period, from the 9th to 19th century. Twenty multi-component medications were selected for the study of ingredients and their active compounds. PubMed, Google Scholar, and Scopus were searched to find pediculicidal or insecticidal evidence. In vitro studies and clinical trials reporting anti-lice and/or insecticidal activities were summarized. Formulations had four kinds of base (oil, vinegar, alcohol, or water). Oils act through occluding the respiratory spiracles of lice. Vinegar loosens the attachment between nits and hair shaft, improving the removal of nits from hair. Essential oil- and tannin-containing plants made up the majority of anti-lice components in the current study. Seventeen out of twenty-seven medicinal plants were reported to have pediculicidal and/or insecticidal activity. Considering the results, further investigation leads to the designing new treatments against pediculosis.